2014
DOI: 10.1063/1.4879099
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of spontaneous hydrogen segregation in LaFe13−xSixHy

Abstract: By means of time-and temperature-dependent magnetization measurements, we demonstrate that the timescale of hydrogen diffusion in partially-hydrogenated LaFe 13−x Si x H y is of the order of hours, when the material is held at temperatures close to its as-prepared Curie temperature, T C0 . The diffusion constant is estimated to be D ≈ 10 −15 -10 −16 m 2 s −1 at room temperature. We examine the evolution of a magnetically phase-separated state upon annealing for 3 days at a range of temperatures around T C0 , a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…at x > 2.4, and |∆S iso | significantly decreases 13 . It has been found that T C can be achieved above room temperature (RT) by interstitial H incorporation 15,[26][27][28][29][30][31][32][33] . T C of the hydrogenated compounds can be precisely tuned near RT by varying Mn substitution [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…at x > 2.4, and |∆S iso | significantly decreases 13 . It has been found that T C can be achieved above room temperature (RT) by interstitial H incorporation 15,[26][27][28][29][30][31][32][33] . T C of the hydrogenated compounds can be precisely tuned near RT by varying Mn substitution [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that, for H composition lower than 1.5 H/f.u. and with T C close to room temperature, there is a splitting into two hydride phases with low and high H concentrations after few hours or weeks at RT [55,74,75]. The sample is no more homogeneous and the magnetic entropy variation is split in two peaks.…”
Section: Combination Of Substitution and Light Element Insertionmentioning
confidence: 99%
“…Although the amount of hydrogen absorbed offers the theoretical potential of targeted TC control, only full hydrogenation is practicable for such first-order (large volume change, sharp magnetic phase transition) compositions due to phase-separate effect where two separate spatial regions with distinctly differing TCs are formed when the material is thermally cycled through the magnetic transition or when it sits close to TC for several days. The origin of this instability is the lattice expansion in the FM state, prompting hydrogen atoms to diffuse from the PM into FM regions of the material that transform first [20]. Partial hydrogenation therefore results in undesirable heterogeneous changes to the samples' properties within very short time scales [21,22].…”
Section: Two Vital Considerations Towards the Implementation Of Magnementioning
confidence: 99%
“…the M(T)properties of sample (A6) have been measured after two months at T = TC + 10 K, then 24 h and 48 h at TC (= 285 K), timescales over which significant hydrogen distribution instability is present in first-order compositions[20], and then finally after repeated fast cycling (15 cycles) across the transition. As shown from the M(H) derivative, only one transition is observed and this is unchanged after all 4 protocols, demonstrating that the properties of partially hydrided samples are stable, behaviour we expect to be general for materials with second-order transitions.…”
mentioning
confidence: 99%